Modul kesihatan mental untuk warga emas - Syed Elias, Sharifah Munirah; Makhtar, Aniawanis (2020)
Modul kesihatan mental untuk warga emas consists of two units; (1) Unit One: Mental health and older people and (2) Unit Two: Strategies to improve mental health promotion in older people. Unit one focuses on the basic understanding related to mental health problems among older people. Unit two focuses on the strategies to improve mental health promotion in older people. This module will be delivered by using a variety of teaching and learning strategies, including seminars and group activities. This will enable learners to utilise up-to-date skills and knowledge and apply them directly in caring for older people.